Exploring the Ligand Functionality, Electronic Band Gaps, and Switching Characteristics of Single Wells–Dawson‐Type Polyoxometalates on Gold. Issue 21 (27th June 2022) - Glöß, Maria; Pütt, Ricarda; Moors, Marco; Kentzinger, Emmanuel; Karthäuser, Silvia; Monakhov, Kirill Yu.
Abstract: The miniaturization, high performance, energy efficiency, and new added functionalities are the essential drivers of modern information data storage and processing technologies. Polyoxometalates (POMs) characterized by atomically well‐defined structures with discrete energy levels and the ability to undergo redox transformations are viewed as promising active components for the integration into the next‐generation (beyond‐CMOS) hybrid nanoelectronics. Herein, new fundamental insights into the application of organically augmented POMs on conducting surfaces are offered. Three key findings resulting from scanning probe investigations combined with integral spectroscopic methods used to explore tris(alkoxo)‐ligated, vanadium‐containing Wells‐Dawson‐type POM structures on Au(111) are reported on. First, it is shown how the (OCH2 )3 C–R ligands, depending on the structurally exposed R group (R = CH2 SMe and NHCOC6 H4 SMe), influence the self‐assembly behavior of the synthesized POMs on gold. Second, the impact of the employed (OCH2 )3 C–R ligands and the determined assembly characteristics on the relative position of POM's electronic band structure against the Fermi level of the gold surface are explained. Third, the on‐surface conductance switching of single POM structures due to external electrical stimuli is demonstrated. The author's experimental efforts enable to discover highly sought‐after multi‐level resistive switching orchestrated by electrically accessible V(3d) states in the POM single‐molecules at room temperature in a narrow voltage range. Abstract : The V3 ‐substituted Wells–Dawson‐type polyoxotungstates equipped with two types of thioether‐augmented tris(alkoxo) ligands are synthesized and deposited as intact molecules from solution on the Au(111) surface, affording ligand‐mediated supramolecular self‐assemblies. The single polyoxometalate molecules show a potential‐induced ligand‐independent multi‐level resistive switching, which is governed by the electrically accessible V(3d) states.